REINTERPRETASI RASIONAL BARAKAH MELALUI MANIFESTASI KHIDMAH DAN TA’DHIM DALAM PERSPEKTIF TEORI PSIKOLOGI ATTACHMENT - M. Aditya Fendik Andriawan; Mohammad Rofiq (Qolamuna : Jurnal Studi Islam, 2026)
In the tradition of Islamic education, the concept of barakah is often perceived as a metaphysical phenomenon that is difficult to measure scientifically, leading to accusations of irrationality or blind obedience amidst the demands of modernity. This study aims to provide a rational re-interpretation of barakah by examining the mechanisms of khidmah (devotion) and ta’dhim (veneration) through the lens of Psychological Attachment Theory. This research employed a qualitative approach with an interdisciplinary-hermeneutic method, synthesizing classical Islamic literature with modern attachment psychology. The findings revealed that barakah can be psychologically redefined as a state of psychological well-being resulting from emotional regulation. Khidmah functions as a channel for proximity seeking that builds mastery experience, while ta’dhim constructs the teacher as a secure base and a safe haven. The synergy between khidmah and ta’dhim forms a secure attachment that empirically enhances students' mental resilience, self-efficacy, and productivity. This study provides an academic justification that traditional pesantren practices have a valid rational basis within the global discourse of mental health psychology. Keywords : Barakah, Khidmah, Ta’dhim, Attachment Theory, Psychological Well-being